GFAP + FOXF2 + ependymal cells promote blood–brain barrier repair via DLL4–NOTCH signaling after neural injury - Qi Xie; Hui Lu; Xiaoman Wang; Siya Wu; Qian He; Mengqi Yuan; Shuang Zhang; Linlin Hu; Changxiong Gong; Xiaofeng Cheng; Yiliang Fang; Zhaoyou Meng; et al. (Proceedings of the National Academy of Sciences, 2026)
Ependymal cells in the adult ventricular-subventricular zone are increasingly recognized for functions extending beyond cerebrospinal fluid dynamics; however, their identity and functional specialization remain incompletely understood. While ependymal cells (EP) have been implicated in interactions with the stem cell niche and the vasculature, their role in repair processes following neural injury remains elusive. In this study, we employed region-specific single-cell transcriptomics of the subventricular zone (SVZ) and ipsilesional peri-infarct territory in mice to identify a distinct subpopulation of GFAP + FOXF2 + EP that selectively expand within the SVZ after neural injury. Notably, these cells were absent from other brain regions. Immunohistochemical validation revealed characteristic ependymal features, including typical pinwheel architecture and expression of Foxj1 and β-catenin. Furthermore, the absence of the proliferation marker Ki67 and the resistance of this subpopulation to Ara-C-mediated ablation indicate that these cells do not possess proliferative properties. Conditional deletion of Foxf2 in GFAP + cells led to impaired endothelial junction integrity and increased blood–brain barrier (BBB) permeability. In contrast, overexpression of Foxf2 via GFAP promoter-driven adeno-associated virus delivery enhanced vascular repair and facilitated functional recovery. Mechanistically, these GFAP + FOXF2 + EP secrete exosomal DLL4, which was associated with enhanced NOTCH pathway activity and restoration of BBB function. While the mechanism linking this limited cell population to the broad reparative effect, particularly the complete signaling amplification cascade, remains to be fully elucidated, these findings identify a subset of EP that contributes to BBB repair.